Development perspectives of the system of aeronavigational service of Ukraine - Беляєвський Л. C.; Лазарев, Г. М.; Харченко, В. П. (Proceedings of National Aviation University (archive), 1998)
Considered are the main shortcomings of the present system of aeronavigational service (ANS). Formulated are the goals and mains directions of improvement of its individual elements. Practical realization of the proposed solutions will allow to integrate the Ukrainian system ANS into European aeronavigation infrastructure